Localization of photoperiod responsive circadian oscillators in the mouse suprachiasmatic nucleus - Tomoko Yoshikawa (Nature Portfolio, 2017)
Abstract The circadian pacemaker in the suprachiasmatic nucleus (SCN) yields photoperiodic response to transfer seasonal information to physiology and behavior. To identify the precise location involved in photoperiodic response in the SCN, we analyzed circadian Period1 and PERIOD2 rhythms in horizontally sectioned SCN of mice exposed to a long or short day. Statistical analyses of bioluminescence images with respective luciferase reporters on pixel level enabled us to identify the distinct localization of three oscillating regions; a large open-ring-shape region, the region at the posterior end and a sharply demarcated oval region at the center of the SCN. The first two regions are the respective sites for the so-called evening and morning oscillators, and the third region is possibly a site for mediating photic signals to the former oscillators. In these regions, there are two classes of oscillating cells in which Per1 and Per2 could play differential roles in photoperiodic responses.